Differential Diagnosis of Chorea—HIV Infection Delays Diagnosis of Huntington’s Disease by Years - Jannis Achenbach; Simon Faissner; Carsten Saft (Brain Sciences, 2021)
Background: There is a broad range of potential differential diagnoses for chorea. Besides rare, inherited neurodegenerative diseases such as Huntington’s disease (HD) chorea can accompany basal ganglia disorders due to vasculitis or infections, e.g., with the human immunodeficiency virus (HIV). The clinical picture is complicated by the rare occurrence of HIV infection and HD. Methods: First, we present a case suffering simultaneously from HIV and HD (HIV/HD) focusing on clinical manifestation and disease onset. We investigated cross-sectional data regarding molecular genetic, motoric, cognitive, functional, and psychiatric disease manifestation of HIV/HD in comparison to motor-manifest HD patients without HIV infection (nonHIV/HD) in the largest cohort of HD patients worldwide using the registry study ENROLL-HD. Data were analyzed using ANCOVA analyses controlling for covariates of age and CAG repeat length between groups in IBM SPSS Statistics V.25. Results: The HD diagnosis in our case report was delayed by approximately nine years due to the false assumption that the HIV infection might have been the cause of chorea. Out of n = 21,116 participants in ENROLL-HD, we identified n = 10,125 motor-manifest HD patients. n = 23 male participants were classified as suffering from HIV infection as a comorbidity, compared to n = 4898 male non-HIV/HD patients. Except for age, with HIV/HD being significantly younger (p < 0.050), we observed no group differences regarding sociodemographic, genetic, educational, motoric, functional, and cognitive parameters. Male HIV/HD patients reported about a 5.3-year-earlier onset of HD symptoms noticed by themselves compared to non-HIV/HD (p < 0.050). Moreover, patients in the HIV/HD group had a longer diagnostic delay of 1.8 years between onset of symptoms and HD diagnosis and a longer time regarding assessment of first symptoms by the rater and judgement of the patient (all p < 0.050). Unexpectedly, HIV/HD patients showed less irritability in the Hospital Anxiety and Depression Scale (all p < 0.05). Conclusions: The HD diagnosis in HIV-infected male patients is secured with a diagnostic delay between first symptoms noticed by the patient and final diagnosis. Treating physicians therefore should be sensitized to think of potential alternative diagnoses in HIV-infected patients also afflicted by movement disorders, especially if there is evidence of subcortical atrophy and a history of hyperkinesia, even without a clear HD-family history. Those patients should be transferred for early genetic testing to avoid further unnecessary diagnostics and improve sociomedical care.